Designing Local Culture-based Canva Narratives to Enhance Reading Skills for Junior High School Students - Like Trisnawati Hardina; Slamet Asari; Nirwanto Maruf (JEELS (Journal of English Education and Linguistics Studies), 2024)
The study aimed to develop culturally relevant reading materials for eighth-grade students at one of the state junior schools in Ponorogo, Indonesia, using Canva as a digital platform. The primary objective was to improve students' reading comprehension by integrating local cultural narratives, such as the stories of Reog Ponorogo and Lake Ngebel, into narrative texts. The research employed the ADDIE model to systematically design and implement these materials, with phases including analysis, design, development, implementation, and evaluation. In the Analysis phase, student needs were assessed through questionnaires, revealing that students struggled with narrative structure and found traditional reading materials disengaging. The Design and Development phases involved creating visually engaging, culturally relevant narrative materials using Canva. The materials were then tested in the classroom, where students interacted with the content through reading tasks and quizzes. Findings showed significant improvements in students' engagement and reading comprehension. Over 80% of the participants reported that the materials were more relatable and easier to understand than traditional texts. The study concluded that integrating local culture into reading materials through digital platforms like Canva enhances both student motivation and learning outcomes.